Structural Model of the Association between Spiritual Health and Self-Esteem in Students of Yazd Farhangian University and the Mediating Role of General Health - Mahmoud Zare' Jamalabadi; Seyed Alireza Afshani (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Spiritual and mental health are the components affecting self-esteem and a necessary feature of every teacher. This study aims at examining the association between spiritual health and self-esteem of students of Yazd Farhangian University and the mediating role of general health in the academic year 2020-2021. Methods: This was an analytical and cross-sectional study conducted on all the students-teachers of Yazd Farhangian University. 323 people were selected as a sample based on Cochran's formula. Data were collected through the Paloutzian, R. F., and Ellison, C. W.'s Spiritual Well-Being Scale (SWBS), Goldberg's General Health Questionnaire (GHQ-28), and the Coopersmith Self-Esteem Inventory (CSEI). To analyze the research data, Pearson correlation coefficient, covariance-based structural equation modeling (CB-SEM), bootstrapping technique, and fit indices for structural equation modeling were employed through SPSS and AMOS 24 at a significance level of less than 0.05. Results: Findings revealed a positive and significant correlation between spiritual health and general health (r= 0.316, p<0/001), as well as between general health and self-esteem (r=0.423, p<0/001). Furthermore, there was a positive and significant association between spiritual health and self-esteem (r=0.339, p<0/01). The findings also emphasized the significance of the general health's mediating role between the spiritual health and self-esteem variables. Conclusions: Considering the significant, positive and strong relationship between spiritual health and general health as well as self-esteem, it is recommended that to enhance the adolescents' spiritual and general health and increase their self-esteem, educational programs be revised and more attention be paid to employ Farhangian University students.